Karakteristik Remaja Terinfeksi HIV yang Memanfaatkan Program Pencegahan Penularan HIV ke Anak di RSUP P Kota Jakarta Timur - Erina Eka Hatini; Eline Charla Sabatina Bingan; Sofia Mawaddah; Aisyah Nurjanah (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Abstract – Cases of adolescents infected with HIV in Indonesia continue to show numbers that show an increase. Ignorance of adolescents is one of the factors driving this increase. Thus the need for insight regarding how HIV is transmitted in order to provide assistance for adolescents to avoid HIV and its transmission to children. Adolescents are categorized as an age with a very high risk of transmission. The rate of HIV transmission from mother to child has increased from year to year. In this case, the government implements the Prevention of HIV Transmission from Mother to Child or known as PPIA. PPIA's first program was the provision of information related to HIV/AIDS to pregnant women during pregnancy checks. This study uses a quantitative approach which is presented descriptively with a sample of 97 adolescents. Data collection was carried out using a questionnaire which was afterwards presented in table form with percentages and cross-tabulations between variables. The results showed that 75% of the respondents were aged 14-16 years, with the majority having high school education (48%), working (54%), and having good knowledge of HIV transmission (71%). Good knowledge is not always directly proportional to a supportive attitude towards the PPIA program. Thus it is necessary to improve integrated antenatal care services related to the integration of counseling services and HIV testing.